Soil structure interaction and the radiation damping: A state-of-the-art review - Yaseen Shayah (Results in Engineering)
This paper introduces the soil-structure interaction (SSI) concept and explores relevant research methodologies and modeling techniques to address SSI challenges. A comprehensive analysis of each model's advantages, disadvantages, and practical applications is conducted. Furthermore, the document summarizes the circumstances under which global standards necessitate the consideration of SSI. Nonlinear finite element modeling is demonstrated, and a thorough discussion of the available models, including comparisons and resolution of differences, is presented. The study also explores damping types in soil, including internal damping (comprising viscous and hysteretic damping) and radiation damping, which involves energy dissipation due to wave propagation towards infinity. Radiation damping techniques are explained in detail, along with their limitations. Finally, recommendations and suggestions for future research are outlined.